Alterations in intramuscular connective tissue in hypertonic muscle: a scoping review - Zhao, Xiaoxiao; Sun, Yunfeng; Fede, Caterina; Pirri, Carmelo; Gong, Wei; Del Felice, Alessandra; Stecco, Carla (Frontiers in Physiology, 2026)
IntroductionMuscle hypertonia is a common symptom in patients with upper motor neuron disorders. To date, the role of intramuscular connective tissue (IMCT) alterations in hypertonic muscle has not been fully explored. This review aimed to identify and characterize alterations in IMCT components in hypertonic muscle in central neurological disorders.MethodsThis scoping review included studies investigating IMCT alterations in hypertonic muscles resulting from central neurological disorders. Four electronic databases, including PubMed/Medline, CINAHL, Web of Science, and Scopus, were searched to identify relevant studies published prior to 20 July 2025. The review followed the Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) checklist. The risk of bias was evaluated using ROBINS-E. Data were extracted and narratively synthesized according to IMCT categories.ResultsTwelve studies were included. Among the included studies, increased collagen, glycosaminoglycan content, fascia thickness, and fibroblasts, as well as altered IMCT structural properties, were found in hypertonic muscles. The collagen content was found to be positively correlated with spasticity and stiffness. A key limitation of these studies is that all participants were in the chronic stage of the neurological disease.ConclusionThis scoping review provides evidence that alterations in IMCT components in muscle with hypertonia occur across different neurological conditions. Targeting these changes may provide a new intervention strategy to reduce muscle stiffness and improve the muscle function of patients with hypertonia secondary to neurological disease.